The Time Burden of Specialty Clinic Visits in Persons With Neurologic Disease: A Case for Universal Telemedicine Coverage - Solomon, Daniel L.; Dirlikov, Benjamin; Shem, Kazuko L.; Elliott, Christopher S. (Frontiers in Neurology, 2021)
Objective: Those with chronic neurologic disorders are often burdened not only by the condition itself but also an increased need for subspecialty medical care. This may require long distance travel, while even small distances can be a hardship secondary to impaired mobility and transportation. We sought to examine the burden of time associated with clinical visits for those with chronic neurologic disorders and their family/caregivers. These topics are discussed as an argument to support universal coverage for telemedicine in this population. Design: Cohort Study. Setting: Specialty clinic at community hospital. Participants: 208 unique patients with chronic neurologic disability at physical medicine and rehabilitation or neurourology clinic over a 3-month period. Main Outcome Measures: Patient survey on commute distance, time, difficulties, and need for caregiver assistance to attend visits. Results: Approximately 40% of patients were covered by Medicare. Many patients (42%) perceived it difficult to attend their clinic visit with transportation difficulties, commute time, and changes to their daily schedule being the most commonly cited reasons. Most patients (75%) lived within 25 miles of our clinics and experienced an average commute time of 79.4 min, though 10% required 3 h or more. Additional family/caregiver assistance was required for 76% of patients, which resulted in an inclusive average commute time of 138.2 min per patient. Conclusion: Chronically neurologically-disabled patients and their caregivers may be burdened by the commute to outpatient appointments. To minimize this burden, increased emphasis on telemedicine coverage for those with chronic neurologic disability should be considered by all payors.